2019
DOI: 10.4236/ojbm.2019.72058
|View full text |Cite
|
Sign up to set email alerts
|

A Crossroads for Social Entrepreneurship: Profits versus Ethics

Abstract: This paper reveals one of the most critical challenges faced by Spanish social entrepreneurship: either prioritizing ethical, social and environmental objectives or profit-seeking. Social entrepreneurship (those initiatives that pursue social and environmental objectives as well as economic ones) has become a very celebrated sector welcomed by political leaders, international corporations, large financial actors and the public opinion alike. The motto that another economy is possible is gaining momentum while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
1
0
2
Order By: Relevance
“…17 This research clearly indicates that SEHVs create ethical cultures with principled leadership (PL), and successfully maintain them with business ethics (BE), contributing to "...a more ethical and socially inclusive capitalism." Principled leadership (PL) and business ethics (BE) are new yet complementary concepts to Fuentes and Valenzuela-Garcia (2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 This research clearly indicates that SEHVs create ethical cultures with principled leadership (PL), and successfully maintain them with business ethics (BE), contributing to "...a more ethical and socially inclusive capitalism." Principled leadership (PL) and business ethics (BE) are new yet complementary concepts to Fuentes and Valenzuela-Garcia (2019).…”
Section: Discussionmentioning
confidence: 99%
“…SE and SEHVs face many challenges in running their ventures, among many, these include running a hybrid organization, Baporikar (2016), as well as prioritizing ethical, social and environmental objectives, Fuentes and Valenzuela-Garcia (2019). This research introduces new models of managing such tensions and challenges, namely principled leadership (PL) and business ethics (BE).…”
Section: Discussionmentioning
confidence: 99%
“…For maximum benefit to students, strategies to address networking, inter-disciplinarity, and entrepreneurship must be embedded in the culture that research students experience throughout their research degree programme [ 43 ]. Moreover, since the economic crisis of 2008, the field of social entrepreneurship has experienced a considerable boom [ 44 ]. The study of Chien-Chi et al [ 45 ], who analyzed the relationship between college students' emotional competences, entrepreneurial self-efficacy, and entrepreneurial intention, showed that socio-emotional competence has a positive effect on entrepreneurial intention; moreover, all dimensions of entrepreneurial self-efficacy were significantly and positively correlated with entrepreneurial intention.…”
Section: Discussionmentioning
confidence: 99%
“…Este setor responde a um fenômeno emergente e estrutural, uma manifestação de um realinhamento do capitalismo que está alterando as relações de trabalho, a compreensão do bem público/comum e da maneira pela qual o valor econômico é criado e extraído. (VALENZUELA-GARCIA;FUENTES, 2019, p. 849, tradução nossa) As origens e definições do termo, muitas vezes confundido com empreendedorismo empresarial, tiveram suas bases difundidas fora do Brasil, mas também existem importantes autores e definições que discorrem sobre a temática. Fonte: adaptação de Oliveira (2004, p. 12) Além das definições expostas por OLIVEIRA ( 2004), outros autores compartilham da mesma linha de pensamento a respeito das expressões e objetivos do perfil empreendedor: "O empreender socialmente está relacionado com a criação de um negócio ou projeto que visa colaborar com a resolução de problemas sociais, geração de impacto positivo e obtenção de lucro" (OLIVEIRA; SILVA, 2018, p. 440).…”
Section: Empreendedorismo Social (Es)unclassified